2019
DOI: 10.1111/1759-7714.13169
|View full text |Cite
|
Sign up to set email alerts
|

EGFR T790M detection in formalin‐fixed paraffin‐embedded tissues of patients with lung cancer using RNA‐based in situ hybridization: A preliminary feasibility study

Abstract: Background Following drug resistance in patients with lung cancer treated by EGFR TKIs, a biopsy is required to obtain sufficient cancer tissue for T790M detection in order to select potential beneficiaries suitable for third‐generation EGFR TKIs, such as osimertinib. The purpose of this study was to explore the feasibility of using a new in situ analysis technique based on RNA target sequences to detect EGFR T790M in lung cancer. Methods A total of 28 formalin‐fixed paraffin‐embedded (FFPE) samples from 24 lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Osimertinib is effective for patients who have EGFR T790M mutations and can exert selective pressure, resulting in an increase in pre-existing T790M wild-type clones with additional EGFR-independent resistance mechanisms. This makes them more visible than T790M mutant cells in primary "T790M positive tumors", which may further result in the loss of T790M under resistance to Osimertinib [30]. Consistent with this hypothesis, we statistically analyzed the results of second-generation sequencing of tumors that have lost T790M mutations and found multiple EGFR-independent resistance mechanisms, such as alternative signaling pathways for bypassing activation and histological transformation [31,32].…”
Section: Discussionsupporting
confidence: 56%
“…Osimertinib is effective for patients who have EGFR T790M mutations and can exert selective pressure, resulting in an increase in pre-existing T790M wild-type clones with additional EGFR-independent resistance mechanisms. This makes them more visible than T790M mutant cells in primary "T790M positive tumors", which may further result in the loss of T790M under resistance to Osimertinib [30]. Consistent with this hypothesis, we statistically analyzed the results of second-generation sequencing of tumors that have lost T790M mutations and found multiple EGFR-independent resistance mechanisms, such as alternative signaling pathways for bypassing activation and histological transformation [31,32].…”
Section: Discussionsupporting
confidence: 56%
“…Previously, there are two studies that show the potential of this in situ technology for clinical applications in oncology field. The one demonstrated the prognostic value of POLE mutation identified by this assay in uterine cancer, 30 and the other study showed the assay as a tool for discovery of biomarker of EGFR inhibitor in lung cancer 31 . Moreover, this method could be applied as a biomarker for KRAS inhibitor which has been recently clinically applied to cancers with KRAS p.G12C 32,33 .…”
Section: Discussionmentioning
confidence: 86%
“…The one demonstrated the prognostic value of POLE mutation identified by this assay in uterine cancer, 30 and the other study showed the assay as a tool for discovery of biomarker of EGFR inhibitor in lung cancer. 31 Moreover, this method could be applied as a biomarker for KRAS inhibitor which has been recently clinically applied to cancers with KRAS p.G12C. 32,33 Therefore, RNA-based in situ mutation detection assay can be used for a detection of biomarker and a prediction of prognosis in clinical practice.…”
Section: Ta B L Ementioning
confidence: 99%
“…The EGFR-T790M point mutation accounts for most of the genomic alterations (30–60%) leading to secondary acquired resistance in EGFR-mutated NSCLC patients receiving a course of erlotinib therapy [ 32 , 33 ]. Tissue rebiopsy for EGFR-T790M mutation tests is often required in these patients with acquired resistance to erlotinib therapy [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR-T790M point mutation accounts for most of the genomic alterations (30–60%) leading to secondary acquired resistance in EGFR-mutated NSCLC patients receiving a course of erlotinib therapy [ 32 , 33 ]. Tissue rebiopsy for EGFR-T790M mutation tests is often required in these patients with acquired resistance to erlotinib therapy [ 32 , 33 ]. The third-generation EGFR-TKI osimertinib is an effective subsequent targeted therapy for lung adenocarcinoma patients with secondary EGFR-T790M mutations after erlotinib treatment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%